2015
DOI: 10.7251/afts.2015.0712.067r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmental Conditions on Carbon and Nitrogen Content in Serbian Rendzina Soils

Abstract: Organic matter in Serbian Rendzina soils dependence on altitude and geographic regions was investigated. There was no regular dynamics of carbon and nitrogen content nor in C/N ratio, probably because of slight climatic variation among altitudes and regions, thus negligible differences in vegetation, organic litter and decomposition dynamics. Predicted climatic changes, uneven for regions, will exert a complex influence on soil C and N storage. These results should be used as a base for future monitoring of C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some authors found no differences among various altitudes [18]. Climatic conditions on various altitudes in Serbia are not different enough to cause significant influence on organic matter composition, neither on organic matter content [19].…”
Section: Discussionmentioning
confidence: 97%
“…Some authors found no differences among various altitudes [18]. Climatic conditions on various altitudes in Serbia are not different enough to cause significant influence on organic matter composition, neither on organic matter content [19].…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed that higher amounts of SOM were accumulated in the meadow than in the forest soils, which is consistent with the findings of Saviozzi et al (2001). In various regions of the world, however, higher C org contents, and thus SOM, have been reported in forest rather than meadow soils (Lemma et al 2006;Grunzweig et al 2007;Radmanović et al 2015). The discrepancies between these findings result from the different species and ages of the forests, which affect the amount of residues accumulating from the trees.…”
Section: Evaluation Of the Impact Of Afforestation On Som Propertiesmentioning
confidence: 98%
“…Tree species affect the quantity and quality of soil organic matter (SOM), and the properties and processes that determine soil fertility, such as pH, sorption complex composition, nutrient cycling and biological activity (Beas et al 2019). An important factor influencing the degree of such changes is the time passed after afforestation of grasslands (Radmanović et al 2015). As an indicator of the changes occurring in soils, including their fertility, an assessment of dehydrogenase activity (DHA) is often used because this represents the total soil microbial activity, and is rapidly reactive to any change (Salazar et al 2011;Veres et al 2013).…”
Section: Introductionmentioning
confidence: 99%